2011
DOI: 10.1111/j.1471-0528.2011.03055.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of adverse perinatal outcomes in women with asthma

Abstract: Background Asthma is a common condition during pregnancy and may be associated with adverse perinatal outcomes.Objective This meta-analysis sought to establish if maternal asthma is associated with an increased risk of adverse perinatal outcomes, and to determine the size of these effects.Search strategy Electronic databases were searched for the following terms: (asthma or wheeze) and (pregnan* or perinat* or obstet*).Selection criteria Cohort studies published between 1975 and March 2009 were considered for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
159
5
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(178 citation statements)
references
References 78 publications
10
159
5
4
Order By: Relevance
“…Our results are in line with previous human studies on short-term reproductive failures after asthma during pregnancy, which have shown associations of asthma during pregnancy with adverse obstetric outcomes and congenital malformation, [4][5][6] and extend knowledge to an overview of potential long-term consequences. Indeed, previous studies on long-term consequences of asthma during pregnancy with regard to selected child diseases also demonstrated an increased risk of asthma, bronchiolitis, atopic dermatitis, and autism spectrum disorder, in offspring of mothers with asthma.…”
Section: Figuresupporting
confidence: 81%
See 1 more Smart Citation
“…Our results are in line with previous human studies on short-term reproductive failures after asthma during pregnancy, which have shown associations of asthma during pregnancy with adverse obstetric outcomes and congenital malformation, [4][5][6] and extend knowledge to an overview of potential long-term consequences. Indeed, previous studies on long-term consequences of asthma during pregnancy with regard to selected child diseases also demonstrated an increased risk of asthma, bronchiolitis, atopic dermatitis, and autism spectrum disorder, in offspring of mothers with asthma.…”
Section: Figuresupporting
confidence: 81%
“…2,3 A recent meta-analysis, including 40 publications from cohort studies, showed that maternal asthma was associated with an increased risk of low birth weight, small for gestational age, preterm delivery, and preeclampsia. 4 Moreover, in a cohort including .40 000 pregnancies, maternal asthma during pregnancy was related to an increased risk of any congenital malformation in the offspring, and, specifically, to an increased risk of malformations of the nervous system, respiratory system, and digestive system. 5 Maternal asthma during pregnancy was also shown to play a role in cardiac malformations in the offspring.…”
mentioning
confidence: 99%
“…Worldwide, asthma represents one of the most common chronic diseases to affect pregnancies, affecting between 8 and 13 % of the population (1)(2)(3) . A meta-analysis from 2011 demonstrated that asthma in pregnancy was associated with up to 54 % increased risk for low birth weight, small for gestational age, preterm delivery and pre-eclampsia (4) .…”
Section: Pre-conception Diet Asthma Factor Analysis Dietary Patterns mentioning
confidence: 99%
“…Worldwide, asthma represents one of the most common chronic diseases to affect pregnancies, affecting between 8 and 13 % of the population (1)(2)(3) . A meta-analysis from 2011 demonstrated that asthma in pregnancy was associated with up to 54 % increased risk for low birth weight, small for gestational age, preterm delivery and pre-eclampsia (4) .A subsequent meta-analysis revealed that asthma exacerbations in pregnancy increased the risk for low birth weight (relative risk (RR) = 3·02; 95 % CI 1·87, 4·89) and compared with women with mild asthma, women with moderate to severe asthma were at increased risk for babies born with low birth weight (RR = 1·15; 95 % CI 1·05, 1·26) or small for gestational age (RR = 1·24; 95 % CI 1·15, 1·35) (5) . These studies suggest that worsening asthma during pregnancy may contribute to poor outcomes for the fetus and that approaches to improve asthma control may be of benefit (6) .…”
mentioning
confidence: 99%
“…Maternal asthma worsens during pregnancy in ~50% of women, and 20% of asthmatic women undergo exacerbations requiring medical intervention (Murphy et al 2005, Murphy et al 2006. Asthma during pregnancy substantially increases risks of adverse pregnancy outcomes, including preeclampsia (↑54%), preterm birth (↑41%), SGA (↑22%), and LBW (↑46%) (Murphy et al 2011). Risks of adverse neonatal outcomes including admission to neonatal intensive care (↑12%), respiratory distress syndrome (↑9%) and transient tachypnoea of the newborn (↑10%) are also increased when the mother has asthma, even after correction for prematurity as a comorbidity (Mendola et al 2014).…”
Section: Evidence For Maternal Asthma and Allergy During Pregnancy Asmentioning
confidence: 99%